2007
DOI: 10.3934/mbe.2007.4.711
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid multiscale landmark and deformable image registration

Abstract: An image registration technique is presented for the registration of medical images using a hybrid combination of coarse-scale landmark and B-splines deformable registration techniques. The technique is particularly effective for registration problems in which the images to be registered contain large localized deformations. A brief overview of landmark and deformable registration techniques is presented. The hierarchical multiscale image decomposition of E. Tadmor, S. Nezzar, and L. Vese, A multiscale image r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 23 publications
0
20
0
Order By: Relevance
“…The hierarchical, multi-layered (BV,L 2 )-decompositions (1.6) were found to be effective tools in image processing [33,8] and image registration [18,27]. They apply to image denoising in the presence of additive or multiplicative noise, to image deblurring and to image segmentation.…”
Section: Introduction -Hierarchical (Xy ) Decompositionsmentioning
confidence: 99%
“…The hierarchical, multi-layered (BV,L 2 )-decompositions (1.6) were found to be effective tools in image processing [33,8] and image registration [18,27]. They apply to image denoising in the presence of additive or multiplicative noise, to image deblurring and to image segmentation.…”
Section: Introduction -Hierarchical (Xy ) Decompositionsmentioning
confidence: 99%
“…In Ref. 12, we demonstrated that the multiscale registration algorithm is robust with respect to the location of the landmarks. In particular, the accuracy of the multiscale algorithm is not dependent on exact matching of the landmarks; due to the iterative nature of the registration method, we achieve accurate registration results even if the landmark locations are perturbed approximately 10 mm from their exact locations.…”
Section: Iib Landmark-based Registrationmentioning
confidence: 99%
“…12 to register three-dimensional rectum, head-neck, and prostate planning CT and daily CBCT volumes with one another. To evaluate the accuracy of the registration algorithm, we computed the mutual information similarity measure between the planning CT volumes and daily CBCT volumes before registration, after B-splines deformable registration, and after multiscale registration.…”
Section: Iiib2 Three-dimensional Multiscale Registrationmentioning
confidence: 99%
“…This type of approaches can usually obtain more accurate registration results, since the advantages of landmark-based and intensity-based registration can be combined. Different hybrid registration models have also been proposed recently [7,17,26,27,44].…”
Section: Introductionmentioning
confidence: 99%